Electrospin-Coating of Paper: A Natural Extracellular Matrix Inspired Design of Scaffold - Ng, Kelvin Wei Shan; Azari, Pedram; Nam, Hui Yin; Xu, Feng; Pingguan-Murphy, Belinda (MDPI, 2019)
Paper has recently found widespread applications in biomedical fields, especially as an alternative scaffolding material for cell cultures, owing to properties such as its fibrous nature, porosity and flexibility. However, paper on its own is not an optimal material for cell cultures as it lacks adhesion moieties specific to mammalian cells, and modifications such as hydrogel integration and chemical vapor deposition are necessary to make it a favorable scaffolding material. The present study focuses on modification of filter paper through electrospin-coating and dip-coating with polycaprolactone (PCL), a promising biomaterial in tissue engineering. Morphological analysis, evaluation of cell viability, alkaline phosphatase (ALP) activity and live/dead assays were conducted to study the potential of the modified paper-based scaffold. The results were compared to filter paper (FP) and electrospun PCL (ES-PCL) as reference samples. The results indicate that electrospin-coating paper is a simple and efficient way of modifying FP. It not only improves the morphology of the deposited electrospun layer through reduction of the fiber diameter by nearly 75%, but also greatly reduces the scaffold fabrication time compared to ES-PCL. The biochemical assays (Resazurin and ALP) indicate that electrospin-coated filter paper (ES-PCL/FP) provides significantly higher readings compared to all other groups. The live/dead results also show improved cell-distribution and cell-scaffold attachment all over the ES-PCL/FP. © 2019 by the authors.